Targeting Super-Enhancers as a Therapeutic Strategy for Cancer Treatment - Yi He; Wenyong Long; Qing Liu (Frontiers Media S.A., 2019)
Super-enhancers (SEs) refer to large clusters of enhancers that drive gene expressions. Recent data has provided novel insights in elucidating the roles of SEs in many diseases, including cancer. Many mechanisms involved in tumorigenesis and progression, ranging from internal gene mutation and rearrangement to external damage and inducement, have been demonstrated to be highly associated with SEs. Moreover, translocation, formation, deletion, or duplication of SEs themselves could lead to tumor development. It has been reported that various oncogenic molecules and pathways are tightly regulated by SEs. Moreover, several clinical trials on novel SEs blockers, such as BET inhibitor and CDK7i, have indicated the potential roles of SEs in cancer therapy. In this review, we highlighted the underlying mechanism of action of SEs in cancer development and the corresponding novel potential therapeutic strategies. It is speculated that targeting SEs could complement the traditional approaches and lead to more effective treatment for cancer patients.